Oppositional identities and the labor market - Harminder Battu; McDonald Mwale; Yves Zenou (Institute for the Study of Labor (IZA), 2005)
We develop a model in which non-white individuals are defined with respect to their social environment (family, friends, neighbors) and their attachments to their culture of origin (religion, language), and in which jobs are mainly found through social networks. We find that, depending on how strong peer pressures are, nonwhites choose to adopt oppositional identities since some individuals may identify with the dominant culture and others may reject that culture, even if it implies adverse labor market outcomes.
Keywords: A14; J15; 330; ethnic minorities; identity; social networks; white's norm; multiple equilibria; Farbige Bevölkerung; Arbeitsplatzsuchmodell; Arbeitsmarktsegmentierung; Theorie; Soziales Netzwerk